Reading Literacy Culture as a Determining Factor of Social Studies Learning Outcomes in Junior High Schools - Wahyuningsih, Nur; Restian, Arina; Tinus, Agus (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the relationship between reading literacy culture and students’ learning outcomes in Social Studies among seventh-grade students at SMP Negeri 2 Mantingan. The study employed a mixed-methods approach with a correlational research design, integrating quantitative and qualitative methods to obtain a comprehensive understanding of the relationship between the variables. Quantitative data were collected using a questionnaire to measure students’ reading literacy culture, while qualitative data were obtained through structured interviews and observations to explore contextual factors influencing literacy habits and Social Studies learning. Secondary data were derived from official school documents, including students’ test scores and report card records. The population of this study consisted of all seventh-grade students at SMP Negeri 2 Mantingan, totaling 33 students. Due to the relatively small population size, a total sampling technique was applied, in which all members of the population were included as research participants. Data analysis techniques included instrument validity and reliability tests, normality testing, linearity testing, and hypothesis testing using the Pearson Product-Moment correlation with the assistance of SPSS software. The results of the analysis indicated that the data were normally distributed and exhibited a linear relationship. The Pearson Product-Moment correlation test revealed a positive relationship between reading literacy culture and students’ Social Studies learning outcomes, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁). These findings demonstrate that reading literacy culture plays an important role in improving students’ Social Studies learning outcomes. Therefore, strengthening reading literacy culture should be systematically integrated into Social Studies instruction, particularly within the framework of the Merdeka Curriculum.